Erotic Journeys : Mexican Immigrants and Their Sex Lives - González-López, Gloria, 1960- (Book collections on Project MUSE., 2005)
Erotic Journeys is a fascinating, revealing, and respectful examination of the romantic relationships and sex lives of the fastest-growing minority group in the nation. In a series of in-depth interviews, Gloria González-López investigates the ways in which sixty heterosexual Mexican women and men living in Los Angeles reinvent their sex lives as part of their immigration and settlement experiences. Defying a broad spectrum of preconceived notions, these immigrants confirm in their vivid narratives that sexuality-far from being culturally determined-is fluid and complex. Gon.